Frank Einstein and the BrainTurbo - Scieszka, Jon (Scieszka, Jon. Frank Einstein, 2015)
"Frank Einstein (kid-genius, scientist, and inventor) and his best friend Watson, along with Klink (a self-assembled artificial-intelligence entity), and Klank (a mostly self-assembled and artificial almost intelligence entity), once again find themselves in competition with T. Edison, their classmate and archrival--this time in the quest to unlock the power behind the science of the human body"-- Provided by publisher.